Shrimp Presence Level In The Mangrove Ecosystem Area Gampong Alue Naga Syiah District, Kuala City, Banda Aceh - Wahyuna Aulia Utami; M. Ali Sarong; Asiah M. D Asiah M. D; Abdullah Abdullah; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Shrimp is a fishery product that has high economic value and is experiencing ecological pressure due to habitat destruction. This study aims to determine the level of presence of shrimp species and shrimp species that dominate in the Mangrove Ecosystem Area of Gampong Alue Naga, Syiah Kuala District, Banda Aceh City. This study uses an exploratory survey method with purposive sampling technique. The tool used to catch shrimp is Pintur. Observation stations are determined based on water conditions, namely station I is in the middle of the brackish ecosystem, station 2 is close to the coast, station 3 is in a watershed area. The parameters measured in this study consisted of biotic parameters which included the presence and number of shrimp species that dominated and abiotic parameters consisted of water environmental conditions, namely water temperature, salinity, pH. Data analysis was carried out using the Attendance Rate formula and Simpson's Dominance formula. The results of the analysis showed that the species that had the highest level of presence was Jerbung Shrimp (Penaeus merguiensis de Man) with a frequency of presence of 74.07%, while the lowest found was Pistol Shrimp (Alpheus microrhynchus de Man) with an attendance frequency of 29.63%. The dominance values ranged from 0.04 – 0.17 where the lowest dominance was Pistol Shrimp (Alpheus microrhynchus de Man) and the highest was Jerbung Shrimp (Penaeus merguiensis de Man). In conclusion, the high value of the presence of the jerbung shrimp species (Penaeus merguiensis de Man) indicates that the adaptation value and range of this species is very wide. Keywords: Presence level, dominance, shrimp, mangrove zoning, Syiah Kuala District, Banda Aceh City Udang merupakan hasil perikanan yang bernilai ekonomis tinggi dan mengalami tekanan ekologis akibat rusaknya habitat.Penelitian bertujuan mengetahui tingkat kehadiran spesies udang dan spesies udang yang mendominasi di Kawasan Ekosistem Mangrove Gampong Alue Naga KecamatanSyiah Kuala Kota Banda Aceh. Penelitian ini menggunakan metode survei eksploratif dengan Teknik PurposiveSampling. Alat yang digunakan untuk menangkap udang adalah Pintur. Stasiun pengamatan ditentukan berdasarkan kondisi perairanyaitu stasiun I berada di wilayah tengah ekosistem payau, stasiun 2 berada dekat dengan pesisir pantai, stasiun 3 berada di kawasan aliran sungai. Parameter yang diukur dalam penelitian terdiri dari parameter biotikyang meliputi jumlah kehadiran dan jumlah jenis udang yang mendominansi dan parameter abiotikterdiri darikondisi lingkungan perairan yaitu suhu air, salitinas, pH. Analisis data dilakukan menggunakan rumusTingkat Kehadiran dan rumus Dominansi Simpson. Hasil analisis menunjukkan bahwa spesies yang memiliki tingkat kehadiran tertinggi adalah Udang Jerbung (Penaeus merguiensis)dengan nilai frekuensi kehadiran 74,07%, sedangkan yang paling rendah ditemukan ialah Udang Pistol (Alpheus microrhynchus) dengan frekuensi kehadiran 29.63%. Nilai dominansi berkisar antara 0,04 – 0,17 dimana dominansi terendah spesies Udang Pistol (Alpheusmicrorhynchus) dan tertinggi adalah Udang Jerbung (Penaeus merguiensis). Tingginya nilai dominansi spesies udang jerbung (Penaeus merguiensis)menunjukkan bahwa nilai adaptasi dan kisaran dari spesies tersebut sangat luas. Kata kunci:Tingkat kehadiran, dominansi, Udang,Zonasi Mangrove Kecamatan Syiah Kuala Kota Banda Aceh